2014
DOI: 10.1016/j.cma.2014.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Ideal minimal residual-based proper generalized decomposition for non-symmetric multi-field models – Application to transient elastodynamics in space-time domain

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. b s t r a c tIt is now well established that separated representations built with the help of proper generalized decomposition (PGD) can drastically reduce computational costs associated with solution of a wide variety of problems. However, it is still an open question to know if separated representations can be efficiently used to approximate solutions of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Energy measure for displacements: Similar to previous works of Giacoma et al [17,21] and Boucinha et al [22], the energy measure related to displacements is evaluated in order to determine the size of the reduced basis. The energy measure of the displacement field integrated over the considered time domain is defined by…”
Section: Mode Selection Of the Reduced Basismentioning
confidence: 99%
“…Energy measure for displacements: Similar to previous works of Giacoma et al [17,21] and Boucinha et al [22], the energy measure related to displacements is evaluated in order to determine the size of the reduced basis. The energy measure of the displacement field integrated over the considered time domain is defined by…”
Section: Mode Selection Of the Reduced Basismentioning
confidence: 99%
“…The gauging condition is satisfied when Dirichlet conditions are applied to A ϕ . Equation (8) can, thus, be simplified into a scalar function…”
Section: Coupled Nonlinear Dynamic Problem a Magnetic Problemmentioning
confidence: 99%
“…Moreover, the representation of unknown dynamic especially on mechanics. For instance, it is employed to solve the problems of rheology [5], viscoelasticity [6], fluid flow [7], and elastodynamics [8]. A dedicated review is found in [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy of the ROM strongly depends on the relevancy of the selected RB [15,19,20]. Contrary to the POD-based ROM method, the proper generalized decomposition (PGD)-based ROMs [21] have been more recently generalized to high-dimensional problems [22][23][24][25][26][27]. The aim of PGD is to approximate a space-time solution as a sum of products of space and time functions, and the PGD method is usually coupled with the nonlinear non-incremental LATIN solver [21] over the entire time interval.…”
Section: Introductionmentioning
confidence: 99%